Business Groups in Ecuador: a Historical, Economic and Political Analysis - Vanoni Martínez, Giuseppe; Rodriguez Romero, Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article aims to analyze the historical influence of the business conglomerates on Ecuador, especially during the period 1965 to 2000. Through the Quivy and Van Campenhoudt methodological process were identified the different theoretical approaches of the conglomerates. Then, the period of study was divided into stages that explain in a historical way how agricultural exporters, traders, industrialists and bankers were getting involved trough pacts and pressures into the Ecuadorian economy and politics. As a result, the conglomerates have had a historical influence on the political and economic areas from the most basic modes of accumulation like the estate. In conclusion, the business conglomerates in Ecuador have been linked to the different civilian and military governments handling in a direct or indirect way, the most vulnerable political and economic moments of the country.